Factors influencing the outcome of cardiogenic cerebral embolism: a literature review. (4th March 2022) - Wang, Yanling; Haddad, Yazeed; Patel, Radhika; Geng, Xiaokun; Du, Huishan; Ding, Yuchuan
ABSTRACT: Objective: The onset of cardiogenic cerebral embolism is sudden, dangerous, and often has high morbidity and mortality. Improving understanding of factors contributing to outcomes of cardiogenic cerebral embolism will improve prognostic and therapeutic capabilities. Methods: Through PubMed and Google Scholar, this paper examined and analyzed the factors implicated in the outcome of patients with cardiogenic cerebral embolism using the key terms 'cardiogenic cerebral embolism', 'atrial fibrillation', 'stroke related diseases', 'collateral circulation', 'emboli profile', 'epigenetic' up to 28 February 2021. Full texts of the retrieved articles were accessed. In general, in these literatures, National Institute Health of Stroke Scale (NIHSS) score ≥ 17, modified Rankin Scale (mRS) score ≥ 2, stroke recurrence, death caused by stroke are regarded as the criteria of poor prognosis. As long as one of these conditions occurs, it is judged as poor prognosis. Results: Factors influencing patient outcomes including patient outcome include severity of neurological impairment, types and severity of combined heart diseases, establishment of cerebral collateral circulation, treatments, components of emboli causing cardiogenic cerebral embolism, existence and control of other system complications, distribution and expression of inflammatory immune cells and molecules in the course of cardiogenic cerebral embolism, and epigenetic changes related to disease prognosis. Conclusion: Regarding to prevention and treatment of cardiogenic cerebral embolism, the related factors, such as clinical setting, emboli pathological profile, and epigenetic changes should be emphasized so that outcomes and recurrence of cardiogenic cerebral embolism can be improvised. Abstract : uf0001